Nectar secretion dynamic links pollinator behavior to consequences for plant reproductive success in the ornithophilous mistletoe Psittacanthus robustus - Guerra, T. J. (2014)
The mistletoe Psittacanthus robustus was studied as a model to link flower phenology and nectar secretion strategy to pollinator behaviour and the reproductive consequences for the plant. The bright-coloured flowers presented diurnal anthesis, opened asynchronously throughout the rainy season and produced copious dilute nectar as the main reward for pollinators. Most nectar was secreted just after flower opening, with little sugar replenishment after experimental removals. During the second day of anthesis in bagged flowers, the flowers quickly reabsorbed the offered nectar. Low values of nectar standing crop recorded in open flowers can be linked with high visitation rates by bird pollinators. Eight hummingbirds and two passerines were observed as potential pollinators. The most frequent flower visitors were the hummingbirds Eupetomena macroura and Colibri serrirostris, which actively defended flowering mistletoes. The spatial separation between anthers, stigma and nectar chamber promotes pollen deposition on flapping wings of hovering hummingbirds that usually probe many flowers per visit. Seed set did not differ between hand-, self- and cross-pollinated flowers, but these treatments set significantly more seeds than flowers naturally exposed to flower visitors. We suggest that the limitation observed in the reproductive success of this plant is not related to pollinator scarcity, but probably to the extreme frequency of visitation by territorial hummingbirds. We conclude that the costs and benefits of plant reproduction depend on the interaction strength between flowers and pollinators, and the assessment of nectar secretion dynamics, pollinator behaviour and plant breeding system allows clarification of the complexity of such associations.